Fe/MOF based platform for NIR laser induced efficient PDT/PTT of cancer - Liang, Zixing; Li, Xiaofeng; Chen, Xiaofang; Zhou, Jiawei; Li, Yanan; Peng, Jianhui; Lin, Zhousheng; Liu, Gai; Zeng, Xiancheng; Li, Cheng; Hang, Lifeng; Li, Hailiang (Frontiers in Bioengineering and Biotechnology, 2023)
Photodynamic therapy (PDT) and photothermal therapy (PTT) are widely used in the treatment of tumors. However, their application in the treatment of clinical tumors is limited by the complexity and irreversible hypoxia environment generated by tumor tissues. To overcome this limitation, a nanoparticle composed of indocyanine green (ICG) and Fe-MOF-5 was developed. Fe-MOF-5 has the function of simulating catalase, which can promote the decomposition of excessive H2O2 in the tumor microenvironment and produce oxygen to improve the hypoxic environment. The improvement of tumor hypoxia can enhance the efficacy of PDT and PTT. For the composite nanoparticle, we confirmed that Fe-MOF-5 has the best nanozyme activity. In addition, it has excellent photothermal conversion efficiency and generates reactive oxygen species (ROS) under near-infrared light irradiation (808 nm). The composite nanoparticle showed good tumor inhibition effect in vitro and in vivo, which was superior to the free ICG or Fe-MOF-5 alone. Besides, there was no obvious cytotoxicity in major organs within the effective therapeutic concentration. This research not only provides an efficient and stable anti-tumor nano platform, but also has broad application prospects in the field of tumor therapy and provides a new idea for the application of MOF as an important carrier material in the field of photodynamic therapy.